The investment decision-making process of Portuguese venture capital funds: What’s different and what’s the same? - Leonardo, M.; Pereira, R. (Academy of Entrepreneurship Journal, 2022)
Startups have been proliferating in the business landscape despite the capital restrictions that these companies usually face. This competition for capital has created a very sophisticated venture capital industry across the world. Extant literature explains the investment process of venture capital firms in different countries but no work has previously studied the Portuguese industry. To fill this gap, we have conducted an exploratory study in this country using semistructured interviews. Our findings unfold an interactive process with some simultaneous elements. Surprisingly, the startup’s financial track record is not important in the investment decision. This research results represent a contribution to the body of knowledge on the Portuguese VC industry.